World development report 2004 : making services work for poor people - World Bank (World Bank Washington, DC., 2003)
The 26th edition of the World Bank's flagship annual publication focuses on how countries can accelerate progress towards the Millennium Development Goals (MDGs) by making services work for the poor. Success will depend on the ability to translate resources into basic services.A great strength of the Report is that it takes no ideological position on the issue of providing social sector services to poor people and maintains that governments have a key role to play.
osa; 13/07/16; oif 10/08/16
Ref.
Keywords: Economic development; Rural poor -- Services for -- Developing countries; Social service, Rural; Poverty; Public welfare; Developing countries